The role of exercise right heart catheterization to guide pulmonary hypertension therapy in older adults. (28th July 2022) - Mak, Susanna; Kolker, Shimon; Girdharry, Natasha R.; Bentley, Robert F.; Valle, Felipe H.; Gurtu, Vikram; Mok, K. H.; Moric, Jakov; Thenganatt, John; Granton, John T.
Abstract: The spectrum of patients referred for suspected pulmonary arterial hypertension (PAH) includes a population with clinical features suggestive of pulmonary hypertension due to left heart disease (PH‐LHD). Even after right heart catheterization (RHC) performed at rest, it can be a challenge to identify patients who will clearly benefit from PAH drug therapy. Therefore, the objective of this study was to evaluate the role of exercise RHC to influence decisions regarding prescription of PAH drug therapy in this population. A retrospective cohort study was conducted of older adults with risk factors for PH‐LHD and suspected PH referred for exercise RHC. One year follow‐up was conducted to record clinical outcomes, all changes in PAH drug therapy, and changes in patient‐reported quality of life. The final cohort included 61 patients, mean age of 69 ± 10; 44% and 34% had a history of coronary artery disease and atrial fibrillation respectively. Exercise changed the proportional breakdown of hemodynamic diagnoses from 36% No PH, 44% PAH, and 20% PH‐LHD at rest to 15% No PH, 36% PAH, and 49% PH‐LHD. Although a significant proportion of patients were reclassified as PH‐LHD, there was an overall increase in the proportion of patients receiving PAH drug therapy, particularly for those with PAH confirmed by exercise RHC. A total of 11 PAH drug prescriptions were employed before exercise RHC increasing to 24 after ( p = 0.002). Patients receiving PAH therapy demonstrated significant improvement in self‐reported quality of life. Exercise RHC appeared to influence selection of PAH drug therapy.